PENGARUH BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT ACON INDONESIA GUNUNG SINDUR BOGOR - Udin, Kiwamudin; Asep Suherman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. This study aims to determine the effect of workload and job stress on employee performance at the Mekar Baru District Office. The research method used is quantitative with multiple linear regression analysis. The population in this study consists of all employees of the Mekar Baru District Office, with a total sample of 62 respondents selected using a saturated sampling technique. The results show that workload has a positive but insignificant effect on employee performance, with a t-count of 0.718 < t-table 2.002 and a significance value of 0.476 > 0.05. Meanwhile, job stress has a positive and significant effect on employee performance, with a t-count of 5.058 > t-table 2.002 and a significance value of 0.000 < 0.05. Simultaneously, workload and job stress have a significant effect on employee performance, with an F-count of 15.636 > F-table 3.195 and a significance value of 0.000 < 0.05. Therefore, it can be concluded that job stress is the dominant factor influencing employee performance at the Mekar Baru District Office. Keywords: Workload, Job Stress, Employee Performance, Mekar Baru